2013
DOI: 10.1016/j.jpainsymman.2011.12.288
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Survival in Patients With Advanced Cancer Admitted to Home Care

Abstract: Context. Data regarding prognostication of life expectancy in patients with advanced cancer are of paramount importance to patients, families, and clinicians. However, data regarding patients followed at home are lacking.Objectives. The aim of this study was to evaluate the correlation between various factors recorded at the beginning of home care assistance and survival.Methods. A sample of consecutive patients admitted to two home care programs was surveyed. A preliminary consensus was achieved as to the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 22 publications
1
28
2
5
Order By: Relevance
“…ESAS is currently used for symptom screening and monitoring in different palliative care settings, including inpatients,(5254) outpatients,(5558) and home care. (17) Within other branches of oncology, ESAS has been used by medical oncologists,(59, 60) radiation oncologists,(61) surgical oncologists,(62, 63) and gynecological oncologists. (64, 65) Outside of oncology, ESAS has also been adopted for symptom assessment in patients with kidney diseases,(66, 67) heart failure,(68, 69) pulmonary disorders,(70) hepatic diseases,(71) and sickle cell anemia.…”
Section: Present Applicationsmentioning
confidence: 99%
“…ESAS is currently used for symptom screening and monitoring in different palliative care settings, including inpatients,(5254) outpatients,(5558) and home care. (17) Within other branches of oncology, ESAS has been used by medical oncologists,(59, 60) radiation oncologists,(61) surgical oncologists,(62, 63) and gynecological oncologists. (64, 65) Outside of oncology, ESAS has also been adopted for symptom assessment in patients with kidney diseases,(66, 67) heart failure,(68, 69) pulmonary disorders,(70) hepatic diseases,(71) and sickle cell anemia.…”
Section: Present Applicationsmentioning
confidence: 99%
“…39 Malnutrition assessed by either subjective global assessment or other nutritional indices has also been found to be associated with shortened rates of survival. 40-42 A multicenter study showed that a lower baseline body mass index and higher percentage of weight loss were both associated with shorten rates of survival, thus forming the basis for a prognosis-based staging system for cancer anorexia–cachexia.…”
Section: Actuarial Estimation Of Survivalmentioning
confidence: 99%
“…However, data regarding patients followed at home are lacking. In 374 patients admitted to home care programs low systolic blood pressure and high heart rate, male gender, poor KPS score, anorexia, and dyspnea were correlated with a shorter serviva [23].…”
Section: Home Carementioning
confidence: 96%